Literature Review: Technology-Based Educational Management in Learning - Ninda Yenisa; Naira Anzila Putri (International Journal of Educational Evaluation and Policy Analysis, 2024)
Modern education has undergone significant transformation with the integration of technology into learning. Technology plays a crucial role in enhancing motivation, creativity, and learning effectiveness through interactive media, digital applications, and online platforms. This review employs a literature study method to analyze the impact of technology on learning processes. The analysis reveals that technology facilitates access to information, increases student engagement, and enriches teaching strategies. However, challenges such as technological access gaps in remote areas, limited teacher competencies, and potential negative impacts like internet addiction and reduced communication skills persist. Hence, strategic approaches, including teacher training and infrastructure development, are needed. This study highlights the importance of wise implementation of technology to support inclusive and sustainable education.